Tyrosine phosphorylation of glutamate receptors by non-receptor tyrosine kinases: roles in depression-like behavior - Mao, Li-Min (Neurotransmitter (Houst), 2016)
Several key members of the non-receptor tyrosine kinase (nRTK) family are abundantly present within excitatory synapses in the mammalian brain. These neuron-enriched nRTKs interact with glutamate receptors and phosphorylate the receptors at tyrosine sites. The N-methyl-D-aspartate receptor is a direct substrate of nRTKs and has been extensively investigated in its phosphorylation responses to nRTKs. The α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptor is the other glutamate receptor subtype that is subject to nRTK-mediated tyrosine phosphorylation. Recently, group I metabotropic glutamate receptors (mGluR1/5) were found to be sensitive to nRTKs. Robust tyrosine phosphorylation may occur in C-terminal tails of mGluR5. Tyrosine phosphorylation of glutamate receptors is either constitutive or induced activity-dependently by changing cellular and/or synaptic input. Through inducing tyrosine phosphorylation, nRTKs regulate trafficking, subcellular distribution, and function of modified receptors. Available data show that nRTK-glutamate receptor interactions and tyrosine phosphorylation of the receptors undergo drastic adaptations in mood disorders such as major depressive disorder. The remodeling of the nRTK-glutamate receptor interplay contributes to the long-lasting pathophysiology and symptomology of depression. This review summarizes the recent progress in tyrosine phosphorylation of glutamate receptors and analyzes the role of nRTKs in regulating glutamate receptors and depression-like behavior.